Emotionally Engaged Civil Servants: Toward a Multilevel Theory and Multisource Analysis in Public Administration. (September 2020) - Levitats, Zehavit; Vigoda-Gadot, Eran
Excellent public services build on excellent civil servants who are both emotionally intelligent and engaged in their work. This article proposes a conceptual framework for a better understanding of the relationship between public employees and their complex workplaces. We focus on the engagement of civil servants, the role of managers' and employees' emotional intelligence, and on employees' public service motivation (PSM) to provide better services to citizens. We develop three major propositions: (a) the positive effect of employees' emotional intelligence on their engagement, (b) the moderating effect of managers' emotional intelligence on the relationship between their employees' emotional intelligence and engagement, and (c) the moderating effect of employees' PSM on the relationship between public servants' emotional intelligence and their engagement. Our conceptual framework may set the stage for future research on civil servants' engagement and emotional intelligence and their aggregate impact on the quality of government actions and services.